The role of the ubiquitin-editing enzyme A20 in diseases of the central nervous system and other pathological processes - Abbasi, Asghar; Forsberg, Kirsi; Bischof, Felix (Frontiers in Molecular Neuroscience, 2015)
In recent years, the ubiquitin-editing enzyme A20 has been shown to control a large set of molecular pathways involved in the regulation of protective as well as self-directed immune responses. Here, we assess the current and putative roles of A20 in inflammatory, vascular and degenerative diseases of the central nervous system and explore future directions of research.